Leptogenesis in Supersymmetric Economical 3-3-1 Model - Huong, Do Thi; Long, Hoang Ngoc; Thuy, Nguyen Thi (Communications in Physics, 2011)
We study a leptogenesis scenario in which the heavy Majorana neutrinos are produced non-thermally in inflaton decays in the supersymmetric economical \(SU(3)_C\otimes SU(3)_L \otimes U(1)_X\) model with inflationary scenario. The lepton-number violating interactions among the inflaton and right-handed neutrinos appear at the one-loop level, and this is a reason for non-thermal leptogenesis scenario. The bound followed from the gravitino abundance and the cosmological constraint on neutrino mass/the neutrino oscillation data is: \(m_{ u 3} \simeq \frac{0.05}{δ_{eff}}\) eV. By taking the reheating temperature as low as \(T_R= 10^6\) GeV, we get a limit on the ratio of masses of the light heavies neutrino to those of the inflaton to be: \(\frac{M_{R1}}{M_{φ}} = 0.87\).